MUTATION SPECTRUM OF THE GENE KCNQ1 IN RUSSIAN PATIENTS WITH LONG QT SYNDROME - M. E. Polyak; E. A. Ivanova; A. V. Polyakov; E. V. Zaklyazminskaya (Российский кардиологический журнал, 2016)
The primary long QT syndrome (LQTS) is hereditary disorder of cardiac rhythm. More than 15 genetic types of the disease known. Most prevalent is the type of the disorder related to potassium channel KvLQT1.Aim. Analysis of mutation spectrum in the gene KCNQ1, coding α-subunit of potassium channel IKs, collected with specimens of 143 families with LQTS.Material and methods. Clinical part of the study and LQTS diagnostics included a standard range of personal and family histore, ECG, 24-hour Holter monitoring, EchoCG, long-time passive orthostatic test (tilt-test) if indicated. DNA-diagnostics of mutations in the gene KCNQ1 was performed with the method of direct authomatic sequencing by Sanger.Results. LQTS, type 1, was verified in 53 families (37%). There were 39 mutations revealed in the gene KCNQ1. Most mutations were found once per family, only 4 mutations repeated in 3 or more non-related families. Most prevalent mutation c.477+1G>A in heterozygous kind presents with milder course of the disease. Second by prevalence mutation replacement p.A341V points on serious prognosis of the disease and might be regarded as genetic factor of SCD. Relative predominance of mutations was found for exones 2, 5, 6, 7, 8 of gene KCNQ1. About 20% of mutations appeared de novo. Two non-related mutations were found in 5 families (3,5%) probands. In all cases the carriers of two mutations the disease had worse course, than in one mutation carriage.Conclusion. The data on genetic nature of the disease and clinical signs of various mutations in LQTS can be applied for planning of dynamic follow-up and tactics of antiarrhythmic therapy.